PERILAKU PROKASTINASI MAHASISWA DITINJAU DARI LOCUS OF CONTROL - Hartosujono Hartosujono (JURNAL SPIRITS, 2012)
ABSTRACTThis study aims to determine whether the student procrastination behaviors associated with personality Locus Of Control. Procrastination behavior is the behavior of the individuals who do the work before the deadline. Procrastination behavior is often experienced by students as they work on the task, collecting reports, and other college jobs. While the LOC scale is a scale that can identift whether a person has control behavior from internal or external control himself.By using Levenson LOC scale and scale Procrastination at 62 students. With the research subjects to students who have taken at least 4 semesters of education. By using these two scales, wanted to study, whether they have a relationship in behavior and personality.The result is the pattern of internal and external LOC personality with procrastination behavior, both of which have a significant relationship. For the patterned external LOC personality can behave procrastination, because desire is praised, have high ideals and the need to see the existing; model. While the internal LOC also can behave procrastination, because the tasks received less well organized, the lack of assertiveness and lack o ability to control the schedule.Â Keywords: personality patterns LOC, external control, internal control procrastination.